2020
DOI: 10.1186/s12875-020-1090-9
|View full text |Cite
|
Sign up to set email alerts
|

Intensive psychotherapy and case management for Karen refugees with major depression in primary care: a pragmatic randomized control trial

Abstract: Background: Despite an unparalleled global refugee crisis, there are almost no studies in primary care addressing real-world conditions and longer courses of treatment that are typical when resettled refugees present to their physician with critical psychosocial needs and complex symptoms. We studied the effects of a year of psychotherapy and case management in a primary care setting on common symptoms and functioning for Karen refugees (a newly arrived population in St Paul, Minnesota) with depression.Methods… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…Most articles were excluded because they were not conducted in the primary care setting, did not include mental health services or interventions, were not written in English, or were editorials or abstract proceedings. Subsequently, 19 articles were included: Asgary et al, 2006 (study 1); Bertelsen et al, 2018 (study 2); Bosson et al, 2017 (study 3); Dalgaard et al, 2020 (study 4); Dick et al, 2015 (study 5); Schaeffer and Jolles, 2019 (study 6); Ahmad et al, 2017 (study 7); Furler et al, 2010 (study 8); Jensen et al, 2013 (study 9); Kirmayer et al, 2003 (study 10); Samarasinghe et al, 2010 (study 11); McMahon et al, 2007 (study 12); Njeru et al, 2016 (study 13); Northwood et al, 2020 (study 14); Polcher and Calloway, 2016 (study 15); Rousseau et al, 2013 (study 16); Sorkin et al, 2019 (study 17); Weine et al, 2003 (study 18); White et al, 2015 (study 19) [ 24 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Five articles were used as companion reports [ 68 , 69 , 70 , 71 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most articles were excluded because they were not conducted in the primary care setting, did not include mental health services or interventions, were not written in English, or were editorials or abstract proceedings. Subsequently, 19 articles were included: Asgary et al, 2006 (study 1); Bertelsen et al, 2018 (study 2); Bosson et al, 2017 (study 3); Dalgaard et al, 2020 (study 4); Dick et al, 2015 (study 5); Schaeffer and Jolles, 2019 (study 6); Ahmad et al, 2017 (study 7); Furler et al, 2010 (study 8); Jensen et al, 2013 (study 9); Kirmayer et al, 2003 (study 10); Samarasinghe et al, 2010 (study 11); McMahon et al, 2007 (study 12); Njeru et al, 2016 (study 13); Northwood et al, 2020 (study 14); Polcher and Calloway, 2016 (study 15); Rousseau et al, 2013 (study 16); Sorkin et al, 2019 (study 17); Weine et al, 2003 (study 18); White et al, 2015 (study 19) [ 24 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Five articles were used as companion reports [ 68 , 69 , 70 , 71 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…For vulnerable populations, socioeconomic stressors are closely connected to their mental health and can prevent them from benefiting from mental health treatment [ 54 ]. The study by Dalgaard et al [ 54 ] found that it was important to help parents determine the most immediate problems in order to stabilize the family and help them benefit from therapy; we identified two studies that offered social services and case management to patients [ 54 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 7 trials (12%) were fully industry funded, 26 , 29 , 35 , 94 , 97 , 104 , 127 44 trials (77%) had public funders, and 5 (9%) were funded by mixed sources. 50 , 59 , 67 , 83 , 85 Funding sources were not reported in one trial. 91 Most trials were conducted in the United States (35%), followed by the United Kingdom (14%), Australia (7%), and Norway (7%).…”
Section: Resultsmentioning
confidence: 99%
“…The variables used in our study were constrained by the database and contacting subjects was impossible due to subject anonymity. The third limitation is the model’s R 2 of 0.11, which infers that other factors can predict the functional recovery of social participation, e.g., psychotherapy [ 28 ]. Future studies may address different factors.…”
Section: Discussionmentioning
confidence: 99%